Banking Sector Employees’ Morale - Mann, Nimarta; Lehal, Ritu (Gyan Management Journal, 2011)
Banking sector has witnessed policy amendments due to globalization and liberalization, increased competition from more private and multinational banks and new technologies, especially extensive use of computers. This in turn, has meddled with the work patterns of bank employees by way of scheduled time periods for target completion, tremendous work pressures, high demand for performance, threats from competitors, etc., casting a shadow on the banking sector employees’ morale. Employee morale represents the attitudes of the individuals in an organization towards their worl< environment, towards voluntary cooperation to their full capabilities and towards fulfillment of the organizational goals. Resultant low morale from the aforesaid reasons may be fatal to the organization as human relations tend to deteriorate, there is absenteeism, labour turnover, grievances, antagonism towards leadership and ultimately work suffers quantitatively and qualitatively. This study attempts an objective view of employee morale and comparison across three sectors of banks along with a genderbased comparison on the basis of employee morale. Findings would be insightful as to the level of employee morale across above staled parameters and would act as secondary data for further research hopefully towards policies aimed at attaining better level of employee morale and therefore more efficient bank workforce.